Space-Geodetic Techniques - Hu, Xiaogong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on applications of different Space Geodetic Techniques on Earth exploration and geodetic research. The topics range from the classical estimation of Earth observation at high precision, to more comprehensive aims and scales. Special attention is given to the new orbit determination method, development status and service performance of the BeiDou global navigation system, intersystem bias of satellite onboard receiver and precise orbit determination of low-earth-orbit vehicles, ultra-rapid satellite clock offset estimation, variability of GNSS-derived water vapor, refined gravity field modeling in China, local enhancement of marine gravity fields assisted by satellite SAR data, enhanced prediction models of universal time, etc.